2019
DOI: 10.1155/2019/3530659
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Characterization of Six Plants of the Beninese Pharmacopoeia Used in the Treatment of Salmonellosis

Abstract: Recent studies reported interesting ethnopharmacological, antibacterial, and phytochemical data on some medicinal plants used in the traditional treatment of salmonellosis in Benin. Unfortunately, very little data exists on the toxicity of these species. This study aims to evaluate chemical characteristic of six Benin pharmacopoeial plants used in the traditional treatment of salmonellosis in Benin. The acute toxicity of aqueous and ethanolic extracts ofPsidium guajava,Vernonia amygdalina,Cajanus cajan,Phyllan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
3
8
0
1
Order By: Relevance
“…The results of the present study have shown that the 80% methanol leaves extracts of B. corieacea and U. leptocladon was found to be safe in the Swiss albino mice tested. The safety profile of B. coriacea and U. leptocladon leaves extracts noted in this study is comparable with other studies that evaluated toxicology of other Uvaria and Boscia species ( 22 – 24 ).…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study have shown that the 80% methanol leaves extracts of B. corieacea and U. leptocladon was found to be safe in the Swiss albino mice tested. The safety profile of B. coriacea and U. leptocladon leaves extracts noted in this study is comparable with other studies that evaluated toxicology of other Uvaria and Boscia species ( 22 – 24 ).…”
Section: Discussionsupporting
confidence: 87%
“…In the review by Zhao et al [40], R. tomentosa is considered as weak cytotoxicity and its IC 50 value of the ethanol extract was 15-fold higher than the MIC 90 value. In the acute toxicity test, a previous study showed that the aqueous extracts of P. guajava and P. amarus leaves did not induce any mortality or any histological renal and fetal disorders of the treated rats [21]. Using the brine shrimp lethality test, Gyawali et al [41] showed that the crude methanolic extract of the S. wallichii bark was mildly toxic and it was suggested to use for human consumption for drug purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also focused on the potential usages of the traditional medicinal plants for the treatment of some important infectious diseases such as tuberculosis, salmonellosis, or other food poisoning diseases [21][22][23]. In the customary practice, indigenous people use either fresh or dry plant materials to make the medicinal preparations.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Nkoua Badzi et al [ 38 ] reached the same conclusion with regard to the aqueous extract of Rauvolfia vomitoria. Legba et al [ 66 ] showed the safety of aqueous and ethanolic extracts of the leaves of Vernonia amygdalina used in Southern Benin. Ojo et al [ 40 ] and Satish and Ranjana [ 67 ] reported the safety of ethanolic aqueous extracts of the leaves of Manihot esculenta and Ocimum gratissimum , respectively.…”
Section: Discussionmentioning
confidence: 99%